Adult Education for Social Change: Deconstructing Programs and Services for Adult Immigrants - Shibao Guo; Thomas J. Sork (Adult Education Research Conference, 2005)
This research examines the role of adult education in bringing about social change through community development initiatives at SUCCESS, an immigrant community organization in Vancouver. It focuses on: the historical development of SUCCESS, the provision of programs and services, major changes in SUCCESS, and the social forces behind the changes.